Evaluasi Kebijakan Internasional dan Regulasi Penanganan Sampah Antariksa (Space Debbris) - Maria Joito Gultom; Regita Asiah Azzarah; Nurul Ilmi; Ivan Rivaldo; Roy Eka Telaumbanua; Muhammad Arif; Elsa Kardiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Space debris is increasingly becoming a global problem that has the potential to threaten the sustainability of space exploration and satellite operations. This study aims to evaluate the effectiveness of international policies and regulations that have been implemented in handling space debris, and toidentify gaps and challenges in their implementation. The research method used is a literature study, with an analysis of policy documents from international organizations, academic journals, and reports from related research institutions. Data analysis was carried out using the Miles and Huberman approach, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that although there are a number of international agreements, such as the Outer Space Treaty 1967, the Liability Convention 1972, and the Registration Convention 1975, there is no effective law enforcement mechanism in cleaning up space debris globally. The lack of binding regulations and coordination between countries in mitigating space debris are major challenges that must be overcome. This study recommends the establishment of clearer international standards and an effective implementation system to ensure the sustainability of space exploration.